To what extent does sexual dimorphism exist in competitive powerlifters? - Keogh, J. W. L.; Hume, P. A.; Pearson, S. N.; Mellow, P. (Journal of Sports Sciences, 2008)
We examined sexual dimorphism in the anthropometry of 68 Australasian and Pacific powerlifters (14 females, 54 males) who were competing in one of two national or international powerlifting competitions held in New Zealand. All powerlifters were assessed for 37 anthropometric dimensions by ISAK (International Society for the Advancement of Kinanthropometry) Level II and III accredited anthropometrists. While the powerlifters were highly mesomorphic and possessed large girths and bone breadths, both in absolute terms and when expressed as Zp-scores compared through the Phantom (Ross & Wilson, 1974), these characteristics were often more pronounced in male than female lifters. No significant inter-gender differences in any of the measures of adiposity were observed. When normalized through the Phantom, the female and male powerlifters had relatively similar segment lengths and bone breadths, indicating that regardless of gender, competitive powerlifters possess comparable skeletal proportions. These results indicate that although competitive powerlifters exhibit sexual dimorphism for many absolute anthropometric measures, little dimorphism is found for measures of adiposity and for proportional segment lengths and bone breadths. These results further support the importance of anthropometric profiling for powerlifting, and suggest that successful male and female powerlifters will possess similar proportional characteristics.